Role of lymphocytes producing GM-CSF in human spondyloarthritis. (23rd February 2017) - Al-Mossawi, Mohammad Hussein; Ridley, Anna; Chen, Liye; de Wit, Jelle; Bowness, Paul
Abstract: Background: The spondyloarthritides (SpA) are immune-driven inflammatory diseases in which T lymphocytes are thought to have a major pathogenic role. Lymphocytes producing granulocyte-macrophage colony-stimulating factor (GM-CSF) have been shown to be especially pathogenic in murine models of SpA. This study aimed to identify and characterise the role of GM-CSF-producing lymphocytes in human SpA. Methods: Peripheral blood and joint-derived mononuclear cells from adults with SpA and controls (healthy adults and adults with the inflammatory joint disease rheumatoid arthritis) were studied with flow cytometry and time of flight mass cytometry (CyTOF). The role of GM-CSF was also investigated in joint-derived innate lymphoid cells. GM-CSF-producing CD4 lymphocytes were isolated by cytokine capture, and RNA sequencing transcriptomic analysis was used to compare GM-CSF lymphocytes with T helper (Th) 1 and Th17 cells. Findings: An expansion of GM-CSF-producing CD4 and CD8 T cells was noted in the blood and joints of patients with SpA. Flow cytometry and CyTOF showed that CD4 T cells were the main producers of GM-CSF. GM-CSF production occurred both independently and in combination with classic Th1 and Th17 cytokines, with increased numbers of interleukin 17A+GM-CSF+ double-producing CD4, CD8, and natural killer cells. Expansion of type 3 innate lymphoid cells in SpA also occurred, and GM-CSF was abundantly produced by these cells. Transcriptional analysis of GM-CSF+ cells isolated with a novel triple cytokine capture approach suggested that human GM-CSF+ CD4 T cells represent an effector population distinct from Th1 and Th17 cells. Interpretation: GM-CSF is a key effector cytokine in human SpA and may be a valid target for therapeutic intervention. Anti-GM-CSF monoclonal antibodies are currently in phase 3 trials for rheumatoid arthritis and have been shown to be safe in patients. These data would support the use of these antibodies in SpA. Funding: Wellcome Trust clinical PhD award (to MHA-M).